2019
DOI: 10.3389/fpls.2019.00183
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Light Intensity and Phosphorus Nutrition Affect the P Uptake Capacity of Maize and Soybean Seedling in a Low Light Intensity Area

Abstract: To capture more nutrients, root systems of maize ( Zea mays L.) and soybean ( Glycine max L.) exhibit morphological and physiological plasticity to a localized supply of phosphorus (P). However, the mechanisms of the interaction between light intensity and P affecting root morphological and physiological alterations remain unclear. In the present study, the regulation of P uptake capacity of maize and soybean by light intensity and localized P supply was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 79 publications
3
18
0
Order By: Relevance
“…Phosphate uptake at 100% light intensity was not significantly different from 50% light intensity. The results of this study are in line with Zhou et al (2019) that the highest phosphate uptake and dry weight of plants found at high light intensity. Biofertilizer also had a significant effect on phosphate uptake (Table 8).…”
Section: Phosphate Uptakesupporting
confidence: 91%
“…Phosphate uptake at 100% light intensity was not significantly different from 50% light intensity. The results of this study are in line with Zhou et al (2019) that the highest phosphate uptake and dry weight of plants found at high light intensity. Biofertilizer also had a significant effect on phosphate uptake (Table 8).…”
Section: Phosphate Uptakesupporting
confidence: 91%
“…The germination paper-based approach developed by Hund et al [21] required a plastic covering that stuck to the root and required intervention to remove the covering [24]. Although modified forms of this growth pouch have been reported [12,[24][25][26], there is still a knowledge gap yet to be filled in the development of root phenotyping systems and high-throughput screenings of wheat. The wheat accessions selected for this study have never been reported for root variation analysis to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent literature data, we summarised our results in a model according to which the light intensity controls allocation of sugars between the shoot and the root (Fig. 3SA, supplement; Sakuraba et al 2018, van Gelderen et al 2018aZhou et al 2019). Under BRS light, a redirection of assimilates occurs towards the shoot and for flowering.…”
Section: Discussionmentioning
confidence: 99%
“…3SA). Different studies demonstrated that high light intensity and red light can indeed promote nutrient assimilation and induce specific signaling cascades from the shoot to the root which promote root development, as well as exudation of organic acids in the rhizosphere (Cheng et al 2014, Sakuraba et al 2018, van Gelderen et al 2018aZhou et al 2019). These discoveries revealed that light is not only involved in the synthesis and transportation of sugars Fig.…”
Section: Discussionmentioning
confidence: 99%